Analisis Perkembangan Sosial Emosional Anak Usia Sekolah Dasar pada Permainan Berkelompok (Studi Kasus di MI Muhammadiyah Trangsan Gatak) - Kartika, Sofia Nur; Darsinah, Darsinah; Wulandari, Murfiah Dewi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This study aims to analyze the social-emotional development of elementary school-age children involved in group play. The core indicator of social-emotional learning is the use of the Collaborative for Academic, Social, and Emotional Learning (CASEL) theory, which studies children's social-emotional development, including self-awareness, self-management, relationship-building skills, and responsible decision-making. This research uses a qualitative approach with a case study design. This research involved grade 4 students at MI Muhammadiyah Trangsan Gatak. Data was collected through observation, interviews, and documentation methods. This research found that group games such as gobak sodor, naga snake, and sarong volleyball make a significant contribution to students' social-emotional development. Through interactions in these games, children learn about self-confidence, self-regulation skills, positive social behavior, and responsible decision-making. Keywords: Social Emotional Development, Basic Education, Group Games